Pengaruh Inokulum Jamur Glomus Aggregatum Dan Pupuk Fosfat Sp-36 Terhadap PertumbuhanTanaman Tomat (Lycopersicum esculentum, Mill.) pada Tanah Gambut - Siti Khotimah, Sri Wahyuni, Riza Linda, (Jurnal Protobiont, 2013)
This study was aimed to determine the effect of Vesicula Arbuscular Mycorrhizae (VAM) inoculum and phosphate fertilizer SP-36 on the growth of tomato plants (Lycopersicum esculentum, Mill.) on peat. The research was conducted in the Greenhouse and Laboratory of Microbiology of Faculty of Mathematics and Natural Sciences at Tanjungpura University for 3 months (October 2012 to January 2013). The research design used was a Completely Randomized Design (CRD) which consisted of two factors with five replicates: first factor of VAM fungi : Mo (without fungi of VAM) and M1 (with fungi of VAM) and the second factor of phosphate fertilizer SP-36 : P0 (0 g / polybag), P1 (0,4 g / polybag), P2 (0,6 g / polybag), P3 (0,8 g / polybag), P4 (1 g / polybag). The result showed that the interaction of giving fungi of mikoriza and phosphate fertilizer had no significant effect on the growth of tomato plants. The treatment of P4 gave the highest average value on the parameter of observation of plant height 41,680 cm, leaf area 69,400 cm2, fresh weight top plants of tomato 3,028 g and dry weight top plants of tomato 0,233 g, fresh weight roots 0,143 g and dry weight roots 0,026 g.